Fuzzy Methods in Entrepreneurship Research - Michael Olumekor
The use of fuzzy theory has grown across many academic disciplines, including business, management and economics. In entrepreneurship research, methods such as Fuzzy-set Qualitative Comparative Analysis (fsQCA), fuzzy analytic hierarchy process (fAHP), fuzzy Delphi, fuzzy logic and fuzzy Decision Making Trial and Evaluation Laboratory are increasingly used. The emerging nature of these methods necessitates a synthesis of extant research in this field. Therefore, this research study aims to provide a comprehensive review of the growth of fuzzy methods in entrepreneurship via a bibliometric analysis. Using Scopus as the main data source, a systematic approach for data retrieval, screening and analysis was used. The results include a temporal analysis of citations, and analyses of influence and productivity. Furthermore, using a scientific mapping approach, the main thematic clusters and emerging themes are unpacked. Dominant themes include fsQCA, entrepreneurial orientation, female entrepreneurship, sustainability, entrepreneurial intention and innovation. Emerging themes include COVID-19, sports, ecosystems and the configurational approach. This article concludes with suggestions for future research.